T cell immune responses to mycobacterial antigens in Brazilian tuberculosis patients and controls - Antas, P R Z; Cardoso, F L L; Pereira, K C; Franken, K L M C; Cunha, K S; Klatser, P; Sarno, E N; Ottenhoff, T H M; Sampaio, E P (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2005)
Production of IFN-gamma guarantees helpful T cell-mediated immunity against Mycobacterium tuberculosis infection. We have evaluated the in vitro immune responses to M. tuberculosis antigens using IFN-gamma production among 43 Brazilian tuberculosis (TB) patients prior to and after specific treatment, and 18 community controls. Peripheral blood mononuclear cells (PBMC) were cultivated in the presence either of purified protein derivative, ferritin, 10 kDa, 38 kDa, MPT59, Ag85A or Ag85B. Also, the two M. tuberculosis and M. bovis heat-shock proteins (hsp) 65 and 70 kDa were compared, and 5 day supernatants were harvested for cytokine detection by ELISA. The results showed that the overall profile of primary PBMC in response to most M. tuberculosis antigens was well correlated, since high IFN-gamma levels were induced by Ag85A, Ag85B, 38 kDa, ferritin and 10 kDa, as well as M. tuberculosis hsp65 in TB patients. In addition, analysis was carried out of the in vitro expression of activation molecules on lymphocytes, as CD25 and CD69 expression assessed in 17 TB patients showed induction on CD4+ T cells by Ag85B. Overall, significantly low responses were found in untreated, in comparison with the treated TB patients. Furthermore, internal community but not healthy control individuals have higher immune responses than do TB patients.